Transformative Leadership in Equitable Public Management: Advancing Educational Access and Quality in South Papua - Tambaip, Beatus; Tjilen, Alexander Phuk; Ohoiwutun, Yosephina (Journal of Ecohumanism, 2025)
Background/Purpose: This study explores the barriers and opportunities for enhancing educational access and quality in South Papua through equitable public management strategies. The region faces challenges due to geographical, social, and economic factors that impact the implementation of education policies. The study aims to identify these challenges and propose solutions to improve education equity. Methodology: A qualitative case study approach was used to examine public management dynamics in South Papua. Data were collected through in-depth interviews, field observations, and Focus Group Discussions (FGDs) with stakeholders, including government officials, school leaders, teachers, students, and parents. Quantitative surveys were also conducted to complement qualitative data. The data was analyzed using thematic coding and triangulation for reliability and validity. Findings: Key barriers include limited infrastructure, insufficient teaching staff, and socio-economic issues such as poverty and gender inequality. However, opportunities exist, such as government initiatives for infrastructure improvement, inclusive education, and teacher development. Collaboration between government and civil society organizations is essential for addressing these challenges. Originality/Value: This study offers valuable insights into educational management challenges in South Papua, emphasizing the need for a participatory, collaborative approach to create equitable and sustainable education solutions